The Effect of Chloride Ions for Corrosion Resistance of C276 Material in NaCl Solution - Priyotomo, Gadang; Anam, Ahsonul (Piston: Journal of Technical Engineering, 2024)
Hastealloy-C276 is an austenitic nickel-molybdenum-chromium alloy with small amounts of tungsten added. This material is quite familiar and is used in various industrial components. However, this alloy, like other types, is very susceptible to corrosion due to the influence of chloride ions in solution. The corrosion resistance of steel alloy materials was investigated using electrochemical methods including open circuit potential (OCP), Anodic Potentiodyamic (AP) with and Tafel in NaCl solution media. The test parameters carried out were chloride concentration (0.001 M-1M) and pH (2, 7 and 10) values. The test results show that an increase in chloride ion concentration causes a decrease in the OCP value in a negative direction, which indicates a tendency for decreasing of the corrosion resistance for C276. The AP test results show that the pitting potential (Epit) value slowly decreases as the chloride ion concentration increases up to 1 M. On the other hand, the role of pH is very important in changing the corrosion resistance performance. A decrease in pH to 2 causes an increase in the corrosion rate of the material, whereas an increase in pH causes this decrease.